Prediction of mental toughness based on goal orientations of basketball players - Marković Dušan; Zubić Ivana; Milenković Dejan; Milenković Vesna (Fizička Kultura, 2024)
The aim of this research is to establish the connection between goal orientation and mental toughness among young basketball players in the Kecskemet basketball academy. Sample consisted of 149 respondents aged from 12 to 18, 99 men and 50 women. For the research purposes, the TEOSQ questionnaire was used to examine goal orientation and the SMTQ to examine mental toughness. A statistically significant positive correlation was also established between total mental toughness and task orientation, while the results did not show a statistically significant correlation between total mental toughness and ego orientation. A statistically significant positive correlation was found between the dimension of self-confidence and ego and task orientation. A statistically significant negative correlation was found between the dimension of control and ego orientation, while the correlation between the dimension of control and task orientation is not statistically significant. There was also no statistically significant correlation between the consistency and ego and task orientation. The results of the research show that goal orientations are significant predictors of the mental toughness of athletes, which indicates that they must be taken into account when creating interventions to increase mental toughness.